UTILIZAÇÃO DA CÂNULA NASAL DE ALTO FLUXO EM RECÉM-NASCIDOS: REVISÃO BIBLIOGRÁFICA - Débora Alline Ketzer Rosinieski; Daniella Alves Vento (UniEVANGÉLICA, 2018)
Objective: This study is aimed to conduct a bibliographic review about the current evidences of the use of the high flow nasal cannula (HFNC) involving its clinical effects, safety and tolerance of use in newborns. Methods: This is an integrative bibliographic review, including articles from the PubMed, Cochrane, PEDro and SciELO databases, published between 2013 and 2017. Results: Fourteen studies addressing the proposed theme and demonstrating the applicability in newborns were included and analyzed. Most studies demonstrate the applicability of HFNC in premature newborns with respiratory diseases and post-extubation and it is a non-invasive ventilation modality that provides many benefits to the newborn's respiratory system. Conclusions: Our study shows that based on the current evidence of the use of HFNC it is not yet affirmed that this therapy is superior to any other form of non invasive ventilation, but the results demonstrate good clinical effects in newborns and infants, good tolerance and safety of use as long as the patient receives adequate and constant monitoring.